Implementation of the European Union’s Nitrates Directive in Turkey - Yetis, Ulku (Taylor and Francis, 2013)
The European Union (EU)’s Nitrates Directive (ND) (91/676/EEC) aims to reduce water pollution caused or induced by nitrates from agricultural sources and to prevent further such pollution. Turkey being a candidate country to EU requires heavy cost investments in achieving approximation with EU Environmental Acquis. This study provides a description of the technical measures and investment cost assessment related to the implementation of the ND in Turkey. As Turkey has not yet designated nitrate vulnerable zones (NVZs) according to requirements of the EU’s ND, three scenarios were developed to estimate the capital investments needed for implementation of the ND. Based on the developed scenarios, the low-cost scenario designating eight provinces as NVZs and requiring a total investment of EUR 270 millions for the period 2007–2023 has been selected by the Ministry of Environment and Forestry within the EU Integrated Environmental Approximation Strategy for Turkey.